The Low Cost Green Car (LCGC) Program in Islamic Perspective - M. Muhfiatun; Susi Riyantika (Global Review of Islamic Economics and Business, 2016)
Recently the Government of Indonesia makes a program of Low Cost Green Car (LCGC). The purpose of the program is to support the independence LCGC four-wheeled vehicles industry in order to anticipate the trend of increased demand for energy-efficient motor vehicles and reasonably priced. LCGC program is polemical prolonged. Protests came from all circles. Such as Local Officials, to the Economist. Because the program is properly designed like a cheap car city so that it’s bought by urban communities only According to The Ministry of Industry Article 1 (e) that the Green Car is set up with the price of Rp. 95,000,000.00 (ninety five million). In this case, the government intervened by way Ceiling Price although this intervention thresholds given in the event of structural changes in Indonesia's economic fundamentals, but the policy of intervention was assessed inconsistently. Because the car LCGC-called "earmarked" for the people of the lower middle class but are prohibited from using subsidized fuel. With some reason LCGC issuance of policies by the Government, there are some points that are contradicted by the transport and economic conditions in Indonesia. LCGC policy is certainly contrary to the spirit of alleviating transport problems especially congestion that was hit by the crisis. With the tax-free policy by the government, then the purchasing of the low-cost car will be higher. This is in accordance with the law of demand. The impact is congestion will worsen, especially in the knots of Indonesia's major cities. That means it will grow, the use of fuel and air pollution.